Antibacterial and anticancer potential of marine endophytic actinomycetes Streptomyces coeruleorubidus GRG 4 (KY457708) compound against colistin resistant uropathogens and A549 lung cancer cells. (December 2018) - Rajivgandhi, Govindan; Muneeswaran, Thillaichidambaram; Maruthupandy, Muthuchamy; Ramakritinan, Chockalingam Muthiah; Saravanan, Kandasamy; Ravikumar, Vilwanathan; Manoharan, Natesan
Abstract: The aim of the current study is to identify bioactive compound from marine endophytic actinomycetes (MEA) isolated from Gulf of Mannar region, Southeast coast of India. Among the isolated actinomycetes, strain GRG 4 exhibited excellent ability to inhibit isolated colistin resistant (CR) Pseudomonas aeruginosa ( P. aeruginosa ) and Klebsiella pneumoniae ( K. pneumoniae ), which is a emerging threat to the world. The strain was identified as Streptomyces coeruleorubidus GRG 4 (KY457708), based on morphological, biochemical, phenotypic and genotypic characters. The bioactive metabolites present in the methanolic extract were partially purified by TLC and preparative HPLC. The active HPLC fraction 2 showed 15, 20 mm zone of inhibition against both CR P. aeruginosa and K. pneumoniae respectively. Analytical HPLC and FT-IR results of fraction 2 showed with carbonyl group. Both GC-MS and LC-MS results confirmed that the fraction 2 contained chemical constituents of Bis (2-Ethylhexyl) Phthalate (BEP). The compromised structure with loosely integrated and ruptured cell wall of BEP treated CR bacteria were observed by confocal laser scanning microscope (CLSM) and scanning electron microscope (SEM) at 75 μg/mL of minimum inhibitory concentration (MIC) dose. Further, cytotoxic effect of BEP against A549 human lung cancer cells revealed complete inhibition by cell proliferation and apoptosis was observed at 100 μg/mL in 24 h treatment. In addition, irreversible ROS dependent oxidative damage was clearly observed at the IC50 concentration of BEP. The toxicity of BEP was also studied against Vibrio fischeri ( V. fischeri ) and found to be highly toxic after 15 and 30 min of treatment. Based on the results it could be concluded that the identified compound BEP is a potent inhibitor for CR bacteria and A549 lung cancer cells.